A Telemedicine Center Reduces the Comprehensive Carbon Footprint in Primary Care: A Monocenter, Retrospective Study - Krisztina Schmitz-Grosz; Carsten Sommer-Meyer; Philipp Berninger; Elsa Weiszflog; Norbert Jungmichel; David Feierabend; Edouard Battegay (SAGE Publishing, 2023)
Introduction: Telemedicine reduces greenhouse gas emissions (CO 2 eq); however, results of studies vary extremely in dependence of the setting. This is the first study to focus on effects of telemedicine on CO 2 imprint of primary care. Methods: We conducted a comprehensive retrospective study to analyze total CO 2 eq emissions of kilometers (km) saved by telemedical consultations. We categorized prevented and provoked patient journeys, including pharmacy visits. We calculated CO 2 eq emission savings through primary care telemedical consultations in comparison to those that would have occurred without telemedicine. We used the comprehensive footprint approach, including all telemedical cases and the CO 2 eq emissions by the telemedicine center infrastructure. In order to determine the net ratio of CO2eq emissions avoided by the telemedical center, we calculated the emissions associated with the provision of telemedical consultations (including also the total consumption of physicians' workstations) and subtracted them from the total of avoided CO2eq emissions. Furthermore, we also considered patient cases in our calculation that needed to have an in-person visit after the telemedical consultation. We calculated the savings taking into account the source of the consumed energy (renewable or not). Results: 433 890 telemedical consultations overall helped save 1 800 391 km in travel. On average, 1 telemedical consultation saved 4.15 km of individual transport and consumed 0.15 kWh. We detected savings in almost every cluster of patients. After subtracting the CO2eq emissions caused by the telemedical center, the data reveal savings of 247.1 net tons of CO2eq emissions in total and of 0.57 kg CO2eq per telemedical consultation. The comprehensive footprint approach thus indicated a reduced footprint due to telemedicine in primary care. Discussion: Integrating a telemedical center into the health care system reduces the CO 2 footprint of primary care medicine; this is true even in a densely populated country with little use of cars like Switzerland. The insight of this study complements previous studies that focused on narrower aspects of telemedical consultations.